The Effect of Pedagogic Competence and Work Motivation on Job Satisfaction of High School Teachers in Rupat District, Bengkalis Regency, Riau - Mimi Amriza; Anju Nofarof Hasudungan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of pedagogical competence and work motivation on job satisfaction of high school teachers in Rupat District, Bengkalis Regency, Riau. This study uses a survey method, while the type of research is correlational research. This research technique was conducted to analyze the effect of two independent variables, namely pedagogic competence (X1), work motivation (X2), on one dependent variable, namely teacher job satisfaction (Y). The results showed: 1) Pedagogical competence has a positive and significant effect on job satisfaction of high school teachers in Rupat District, Bengkalis Regency; 2) Work motivation has a positive and significant effect on teacher job satisfaction; 3) Pedagogic competence and work motivation together have a positive and significant impact on teacher job satisfaction.